Non-target effects of chlorantraniliprole and thiamethoxam on Chrysoperla carnea when employed as sunflower seed treatments - Gontijo, Pablo C.; Moscardini, Valéria F.; Michaud, J. P.; Carvalho, Geraldo A. (My University, 2015)
The use of systemic insecticides as seed treatments has raised concern about the possible impacts of these products on natural enemies. This study assessed the effects of sunflower seed treatments with chlorantraniliprole and thiamethoxam on Chrysoperla carnea by exposing larvae and adults to sunflower stem segments grown from treated seeds and the nectar secreted by their extrafloral nectaries. Confinement of larvae with stem segments for their entire developmental period had no effect on their survival or any life history parameter, except that the sex ratio of resulting adults was lower in the thiamethoxam treatment than in chlorantraniliprole. However, when adult pairs of C. carnea were exposed to treated stem segments during their maturation period, their subsequent survival and fecundity was significantly reduced by both materials, with thiamethoxam reducing median survival (LT[subscript 50]) and fecundity to a greater degree than chlorantraniliprole. Insufficient offspring were obtained from adults exposed to thiamethoxam to permit assessment of their fitness, but the offspring in the chlorantraniliprole-exposed adults had reduced larval survival relative to controls. The greater impact of seed treatments on adult lacewings may be partly attributable to their greater consumption of extra-floral nectar. Our results indicate that seed treatment with systemic insecticides can cause negative effects on beneficial insects, potentially disrupting their population dynamics, and should not be assumed compatible with biological control and IPM simply because this mode of application limits direct exposure.
Citation: Gontijo, P. C., Moscardini, V. F., Michaud, J. P., & Carvalho, G. A. (2014). Non-target effects of chlorantraniliprole and thiamethoxam on Chrysoperla carnea when employed as sunflower seed treatments. Retrieved from http://krex.ksu.edu
Keywords: Extrafloral nectar; Systemic insecticides; IPM; Green lacewings; Environmental risk assessment